How to live and how to write: The literaryphilosophical present of the Socratic question for the good life (2021)
For several decades, the question of the good life has gained relevance in university philosophical discourse. A striking phenomenon in this context is the publication of works that, created in academia itself, avoid sticking to the conventional scientific writing format and instead integrate literary strategies in their argumentative flow. Paradigmatic examples of this phenomenon are The Art of Living by Alexander Nehamas (1998); Four Meditations on Happiness (Das vollkommene Leben) by Michael Hampe (2009), and Human Dignity: A Way of Living (Eine Art zu Leben: Über die Vielfalt menschlicher Würde) by Peter Bieri (2013), works that until now have gone practically unnoticed in the Spanish-speaking world. The article aims to fill this gap in reception by tracing the interaction between the ethical concepts put forward in each of the three cases and the particular mode of exposure chosen, as well as by tracing the Socratic ancestry to which they appeal declaredly or tacitly. In addition, the thesis that the use of literary elements is a way of facing the modern neutrality of philosophy will be supported, with an emphasis on the authorial voice, when faced with the question of how to live.